Uji Efek Analgetik Infusa Batang Brotowali (Tinospora Crispa (L.) Miers) Pada Mencit Putih Jantan Galur Swiss (Mus Musculus) - Chandra Septian, Prima (2016)
Background: Brotowali's stem (Tinospora crispa (L.) miers) has compounds alkaloid, soft damar, berberin, pati, glikosida pikroretosid, palmatin, bitter substance of pikoretin, harsa, flavonoid and tanin. Flavonoid compound has analgetic effect. Objective: To know the analgetic effect of brotowali's stem infused (Tinospora crispa (L.) miers)on swiss strain of male white mice (Mus musculus). Methods: It was an experimental laboratoric research using postest only with control group design. Animal under investigation was 30 swiss strain of male white mice (Mus musculus) divided into 5 treatment groups, they are group I aquadest negative control, group II positive control ibuprofen (1,04 mg/ kgBW), group III, IV, V: treated with brotowali's stem infused (Tinospora crispa (L.)miers) with the dosage of 7,8 %, 10,4%, 13% respectively. Result of Research: ANOVA test result obtained significant probability value p= 0.000 (p<0.05) it means in that from 5 groups there were two groups with significant difference. Conclusion: The results of this research showed brotowali's stem infused (Tinospora crispa (L.)miers) seeds with the dosage of 7,8 %, 10,4%, 13% had analgetic effect on swiss strain of male white mice (Mus musculus).